An open-label randomised clinical trial to compare the efficacy of dietary caloric restriction and physical activity for weight loss in overweight pet dogs. (January 2019) - Chapman, M.; Woods, G.R.T.; Ladha, C.; Westgarth, C.; German, A.J.
Highlights: First randomised trial comparing efficacy of caloric restriction and increasing physical activity for weight management in dogs. Dietary caloric restriction was more effective than physical activity for controlled weight loss in overweight pet dogs. Triaxial accelerometery documented deliberate increases in a dog's daily exercise routine. Abstract: Canine obesity is usually managed with a combination of dietary caloric restriction and increasing physical activity, but no previous study has compared both of these strategies in a prospective randomised controlled trial. Thirteen overweight dogs (body condition score 6–9/9) were randomised to one of two interventions: dietary caloric restriction or physical activity. The dietary caloric restriction intervention comprised feeding a therapeutic weight loss diet, while the physical activity intervention comprised increasing the dog's current physical activity pattern by at least a third. The primary outcome measure was change in body weight, while secondary outcome measures included change in neck, thorax and abdominal circumference and change in physical activity measured by triaxial accelerometer. Bodyweight decreased significantly with the dietary caloric restriction (median −10% of starting body weight [SBW], 5 to −12%; P  = 0.028) but not with the physical activity intervention (−2% SBW, +3% to −6%; P  = 0.107). Abdominal circumference (dietary caloric restriction: median −12.0%; physical activity: median −7.8%, P  = 0.016) and thoracic circumference (dietary caloric restriction: median −7.5%, P  = 0.031; physical activity: median −3.6%, P  = 0.031) changed significantly in both groups. There was no change in activity levels within the dietary caloric restriction group, but vigorous activity increased significantly in the physical activity group ( P  = 0.016). Dietary caloric restriction was more effective than physical activity for controlled weight loss in overweight pet dogs. Although advising owners to increase their dog's activity by a third led to a modest increase in measured vigorous physical activity, this was insufficient to promote weight loss on its own.